2021
DOI: 10.1155/2021/6663563
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Efficient Correction of Severe Skeletal Class II Division 1 Malocclusion with Intermaxillary Elastics

Abstract: Treatment of Class II malocclusion accompanied with a skeletal discrepancy is challenging. The approach of correction depends on several factors such as the status and pattern of growth, severity of the malocclusion, and patient cooperation. This case report describes a successful management of a 12-year-old young adolescent boy that was presented with a Class II division 1 malocclusion with an underlying skeletal discrepancy in horizontal and vertical dimensions. Growth modification was achieved by means of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
1
0
4
Order By: Relevance
“…In a similar recent study, Kalra et al 14 used Power scope- a fixed functional appliance and found significant skeletal dental and soft tissue changes. Also, Badri 15 in his study reported a mandibular unlocking effect and effective Class II correction with Class II elastics.…”
Section: Discussionmentioning
confidence: 93%
“…In a similar recent study, Kalra et al 14 used Power scope- a fixed functional appliance and found significant skeletal dental and soft tissue changes. Also, Badri 15 in his study reported a mandibular unlocking effect and effective Class II correction with Class II elastics.…”
Section: Discussionmentioning
confidence: 93%
“…Sin embargo, el grupo con Forsus mostro una corrección molar más efectiva comparado con el grupo de pacientes que utilizo ligas intermaxilares, sin diferencias estadísticas. Badri (15) reporto un caso de corrección severa de maloclusión esquelética de clase II primera división mediante el uso de elásticos intermaxilares, topes de mordida anterior y arcos de acero con dobleces de curva reversa con buenos resultados, además de la cooperación del paciente. Estas estrategias, según el autor, ayudaron a extruir los molares, proinclinar los incisivos y facilitar un mayor crecimiento mandibular.…”
Section: Diversos Estudios Han Evaluado La Estabilidad Postratamiento...unclassified
“…El tratamiento de la Maloclusión de Clase II con discrepancia esquelética es uno de los más desafiantes y su tratamiento depende de diversos factores como el patrón de crecimiento, severidad de la maloclusión y la cooperación del paciente (15). Batista et al (16) realizo una revisión sistemática para evaluar los efectos del tratamiento de Clase II división 1 en niños y adolescentes, sus resultados sugieren, aunque con baja evidencia, que el tratamiento temprano es efectivo para reducir la incidencia de trauma oclusal.…”
Section: Introductionunclassified
See 2 more Smart Citations